Politik ekonomi subsektor perkebunan kelapa sawit di Indonesia - Casson, A. (Yayasan Obor Indonesia, 2003)
The Indonesian oil palm subsector expanded rapidly after 1967. Much of this growth has occured in the last decade and posed a significant threat to Indonesia's existing forest cover. It has also displaced local communities and increased social conflict. This chapter attempted to determine where the growth has already occured, what effect this growth has had on forest cover, and the implications of further growth on Indonesia's forests. Over the last decade, oil palm development has primarily occured within Sumatra and increasingly in Kalimantan. Plantations development has been directed to Eastern Indonesia primarily in Kalimantan and Irian Jaya but industry was more interested in developing plantations in Sumatra because it has necessary infrastructure required to process palm oil and labours. This has increased the potential for further expansion to be located within production forest, limited production forest, and, increasingly, protected forest areas. However, companies continue to apply for concessions in Kalimantan and Irian Jaya so that they can gain access to timber readily available in these outher islands. This explains why many oil palm developments are occuring on production forestlands in Kalimantan and Irian Jaya. The allocation of production forestland to oil palm developer has accelerated conversion and environmental degradation.